Application of Chitosan Coating and Liquid Smoke as Antimicrobial Agent in Tuna Fish Pempek - Budaraga, I Ketut; Hermalena, Leffy; Susanti, Susanti (Jurnal Gizi dan Pangan, 2023)
The goal of this study was to see the effect utilizing chitosan coating and liquid smoke had on pempek as an antibacterial. This study was carried out in an exploratory method, with differences in tuna pempek storage period, namely: control=0 days, A=1 day, B=2 days, C=5 days, D=7 days, and E=9 days. The results showed that the longer pempek tuna was stored using chitosan coating with the addition of 1% liquid smoke, the lower the total plate number was compared to without the addition of 1% liquid smoke. The storage time of pempek tuna without liquid smoke yielded results on chitosan coating, with water content ranging from 6.24 to 11.99% and protein content ranging from 3.68 to 11.8%. The Total Plate Count (TPC) test result was ranging from 5x10-4 to 13x10-4 colonies/g. With liquid smoke added, the water content increased to 4.56−10.48%, the protein content increased to 5.43−12.39, and the TPC test resulted in 2.7x10-4-7.3x10-4 colonies/g. According to SNI 7661.1:2013, a storage time of 3 days in the chitosan coating treatment with the addition of liquid is in the acceptable range